THE PRACTICE OF ILLEGAL HEALTH EQUIPMENT DISTRIBUTION IN INDONESIA REVIEWED FROM BUSINESS ETHICS - Angestika Wilandari (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2021)
The emergence of illegally distributed medical devices is certainly not without reason. The expansion of access to health insurance has pushed the need for health services for the people in Indonesia. The high demand for health services will be directly proportional to the need for medical devices that are distributed safely and evenly. Geographical conditions and characteristics and demographic conditions in Indonesia are a real challenge for the distribution of medical devices evenly and according to procedures. The responsibility for distributing medical devices is one form of applying business ethics through applicable policies or regulations. This study examines the practice of distributing medical devices illegally in Indonesia in terms of business ethics using descriptive analysis methods. With limited research time, the study of illegally distributing medical devices does not reflect healthy and ethical activities when viewed from business ethics outside of relaxation of existing regulations.